The Impact of Job Insecurity and Perceived Organizational Support on Turnover Intention: The Mediating Role of Employee Engagement - Noni Gigih Febriati; Zunaidah; Wita Farla (International Journal of Economics Accounting and Management, 2026)
Turnover intention among teachers is an important issue that can affect the stability and quality of education. This study aims to analyze the effect of job insecurity and perceived organizational support on turnover intention, with employee engagement as a mediating variable. This research used a quantitative approach involving 119 teachers as respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that job insecurity has a positive and significant effect on turnover intention, while perceived organizational support has no significant direct effect. Employee engagement negatively and significantly affects turnover intention, but it does not mediate the relationship between job insecurity and turnover intention. However, employee engagement fully mediates the effect of perceived organizational support on turnover intention. The study concludes that employee engagement plays an important role in reducing teachers’ turnover intention